The role of HDAC6 in fibrosis: a novel and effective therapy strategy - Liangliang Zheng; Xiaoyan Zhu; Jiankui Du; Yujian Liu (European Journal of Medical Research)
Abstract Fibrosis is the usual pathological process observed across a broad spectrum of diseases. The mechanisms of fibrosis involve various cells and signaling pathways. Epigenetic regulation, such as histone acetylation, is one of the mechanisms. Among histone deacetylases (HDACs), histone deacetylase 6 (HDAC6) is particularly unique due to its two-domain structure and its presence in the cytoplasm. Apart from its well-known role as a histone modifier, HDAC6 interacts with multiple non-histone substrates, including α-tubulin, heat-shock protein 90 (HSP90), peroxiredoxins, and TGF-β. It also interacts with ubiquitin through noncatalytic functions. Elevated expression of HDAC6 has been observed in fibrotic diseases. Fibrosis is closely related to inflammation. Given that HDAC6 plays the unique link role in both fibrosis process and inflammation, HDAC6 inhibitors represent a new and effective maneuver for addressing fibrotic diseases. In this paper, we review recent advances in understanding the role of HDAC6 in fibrotic diseases affecting multiple organs, including the lung, heart, liver, kidney, and peritoneum. We also examine the effects of HDAC6 inhibitors, providing a valuable reference for future research into fibrosis mechanisms and therapeutic drug development.